Involvement of the Incumbent's Wifes in the 2020 Regional Head Election during the Corona Pandemic - Sa'diyah, Khalimatus (UIN Sunan Ampel Surabaya, 2021)
The purpose of writing this article is to examine how the incumbent wives are involved in the 2020 Regional Head Election amid a pandemic as part of launching their political dynasty. Even if you look at the current Coronavirus, it is feared that the moment of the 2020 Regional Head Election could increase the spread and transmission of the Coronavirus. However, on the other hand, if the 2020 Regional Head Election is continuously postponed, many regions will not have a legitimate leader. The approach of this research is descriptive qualitative, while to obtain data, the author uses secondary data from journals, news, and other relevant sources. Meanwhile, to dissect this case, the writer uses Anne Philips' theory of women's political representation, Schumpeter's concept of procedural democracy, and political dynasties. The analysis process begins with data collection, data reduction, data presentation, and conclusion drawing. The result shows that the implementation of the 2020 Regional head Election during the Corona period, which was attended by prospective leaders of the incumbent's wives, became a moment to increase the role of women in politics and part of the political dynasty.